Comparative analysis of two emerging rice seed bacterial pathogens - Fory Sánchez, Paola Andrea; Triplett, Lindsay; Ballen, Carolina; Bello, Javier; Duitama, Jorge; Aricapa, María Girlena; Prado Patiño, Gustavo A.; Correa, Fernando; Hamilton, John; Leach, Jan E.; Tohme, Joseph M.; Mosquera Cifuentes, Gloria Maria (Scientific Societies, 2014)
Seed sterility and grain discoloration limit rice production in Colombia and several Central American countries. In samples of discolored rice seed grown in Colombian fields, the species Burkholderia glumae and B. gladioli were isolated, and field isolates were compared phenotypically. An artificial inoculation assay was used to determine that, although both bacterial species cause symptoms on rice grains, B. glumae is a more aggressive pathogen, causing yield reduction and higher levels of grain sterility. To identify putative virulence genes differing between B. glumae and B. gladioli, four previously sequenced genomes of Asian and U.S. strains of the two pathogens were compared with each other and with two draft genomes of Colombian B. glumae and B. gladioli isolates generated for this study. Whereas previously characterized Burkholderia virulence factors are highly conserved between the two species, B. glumae and B. gladioli strains are predicted to encode distinct groups of genes encoding type VI secretion systems, transcriptional regulators, and membrane-sensing proteins. This study shows that both B. glumae and B. gladioli can threaten grain quality, although only one species affects yield. Furthermore, genotypic differences between the two strains are identified that could contribute to disease phenotypic differences.